2010
DOI: 10.1074/jbc.m109.068015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Potent Membrane-remodeling Activity of the Epsin 1 N-terminal Homology Domain

Abstract: The mechanisms by which cytosolic proteins reversibly bind the membrane and induce the curvature for membrane trafficking and remodeling remain elusive. The epsin N-terminal homology (ENTH) domain has potent vesicle tubulation activity despite a lack of intrinsic molecular curvature. EPR revealed that the N-terminal ␣-helix penetrates the phosphatidylinositol 4,5-bisphosphate-containing membrane at a unique oblique angle and concomitantly interacts closely with helices from neighboring molecules in an antipara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 46 publications
7
72
1
Order By: Relevance
“…This fact helps explain the remodeling activity of epsin proteins (9,41), which exhibit no apparent special shape, and provides insights into the mechanics of tubulation induced by crowding of proteins and anchored polymers (15,42). We also demonstrated that regardless of the orientation of their N-terminal helices, the proteins may assemble rapidly to induce membrane buds.…”
Section: Discussionmentioning
confidence: 89%
“…This fact helps explain the remodeling activity of epsin proteins (9,41), which exhibit no apparent special shape, and provides insights into the mechanics of tubulation induced by crowding of proteins and anchored polymers (15,42). We also demonstrated that regardless of the orientation of their N-terminal helices, the proteins may assemble rapidly to induce membrane buds.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that upon binding of ENTH to PtdIns(4,5)P 2 , the protein experiences a change in structure in which helix-0 inserts into the lipid bilayer as demonstrated by EPR spectroscopy (22). This increases the surface area of the outer leaflet of the GUV membrane and induces an asymmetry in the two bilayer leaflets facilitating membrane bending by generating spontaneous curvature (26,45).…”
Section: ϫ4mentioning
confidence: 99%
“…ENTH Binding to PtdIns(4,5)P 2 -doped GUVs-ENTH can induce membrane tubulation (22,25). Recently we showed that binding of ENTH to PtdIns(4,5)P 2 -doped and slightly curved pore-spanning membranes results in a reduction of the lateral membrane tension (27).…”
Section: ϫ4mentioning
confidence: 99%
“…Sla2 and HIP1R form dimers via their coiled-coil domains (14,34), and the ENTH domain of mammalian epsin may oligomerize on liposomes in vitro (35). In addition, both proteins bind clathrin and other coat proteins (reviewed in ref.…”
Section: Sla2∆thatch-acb-gfp Ent1∆acbmentioning
confidence: 99%